(untitled) (Global Journal of Human-Social Science, 2020)
Introduction-The role of religious activities in the social reformation and rehabilitation of prison inmates cannot be over-emphasized. Religious groups have been long recognized as important force in the process that led to the preeminence of corrections in offender management. Punishment in human societies was replete with all form of wickedness until the birth of the modern prison system between 18 and 19th century. According to Foucault (1995) before the birth of the modern prison system, punishment was a public spectacle in which the body of the felon was the object of punishment; offenders were tortured, dismembered, amputated, symbolically branded on face or shoulder, exposed alive or dead to public view. Although modern prison system started essentially as a punitive institution, influence of intellectuals such as Beccaria 1819, Bentham 1843, Foucault 1995 etc. and numerous non-governmental organizations (faith, and non-faith based) constitute the critical mass that drove the idea of rehabilitation into the prison system. Consequently, prisons now have to function essentially as a normalizing and persuasive institution of the state albeit it’s coercive nature.